1999
DOI: 10.2138/am-1999-1-219
|View full text |Cite
|
Sign up to set email alerts
|

Biologically induced iron ore at Gunma iron mine, Japan

Abstract: The mineralogy of sedimentary iron ores from the Gunma iron mine are described to evaluate the role of microorganisms and plants in ore formation. The iron ore is composed of nanocrystalline goethite, well-crystallized jarosite and very small amounts of strengite. The ore characteristically occurs as thick-bands of alternating goethite and jarosite bands, thin-bands of different goethite grain sizes, and fossil-aggregate ore rich in moss and/or leaves. Algal fossils are clearly preserved in the goethite bands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
2
30
0
1
Order By: Relevance
“…BIM processes are characterized by the precipitation on and within cells and the mineral grains have no controlled morphology and size distribution (Akai et al, 1999). The results described above suggest that the iron ores might have resulted from BIM processes.…”
Section: Present-day Seepage Systems: An Analogue For Biologically Mementioning
confidence: 96%
See 2 more Smart Citations
“…BIM processes are characterized by the precipitation on and within cells and the mineral grains have no controlled morphology and size distribution (Akai et al, 1999). The results described above suggest that the iron ores might have resulted from BIM processes.…”
Section: Present-day Seepage Systems: An Analogue For Biologically Mementioning
confidence: 96%
“…Many studies have suggested that minerals forming as a result of microbial activity could present special structures, such as spherical aggregates of different sizes Fortin et al, 1998;Akai et al, 1999;Tazaki, 2000Tazaki, , 2005Williams et al, 2005). The TEM-EDS-SAED pictures of the iron ores showed many fibrous or spherical aggregates of goethite or ferrihydrite, respectively (Figs.…”
Section: Present-day Seepage Systems: An Analogue For Biologically Mementioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the Gunma deposit was formed from one of these acidic spring waters. It is considered that the spring water responsible for the ore deposit was probably ferruginous, cold (less than 30°C), and acidic (pH=2-4) (Shiikawa, 1960;Akai et al, 1999). The iron deposit precipitated on the Pleistocene andesitic lava flows and pyroclastic rocks.…”
Section: Geological Background and Sample Descriptionsmentioning
confidence: 99%
“…Among these deposits, the Gunma deposit is the largest sedimentary iron deposit in Japan. A mineralogical study by scanning electron microscopy, X-ray electron microprobe, and transmission electron microscopy was done recently for the deposit and the iron ore was interpreted as a product of biologically induced mineralization (BIM) (Akai et al, 1999).…”
Section: Introductionmentioning
confidence: 99%